Respuesta :
the point-slope form of a line is given by: y - y1 = m(x - x1). Substituting the given point, (6, -8), and the slope, -2, gives:
y - (-8) = -2 * (x - 6)
This becomes:
y + 8 = -2x + 12
y - (-8) = -2 * (x - 6)
This becomes:
y + 8 = -2x + 12
Answer:y+1=6(x-4)
Step-by-step explanation:
In the question you are already given the information needed, so you don't have to really solve anything further. All you have to do is input it into the point-slope form equation y-y1=m(x-x1) from x1=4 y1=-1 and m=6, giving you y+1=6(x-4). If you're wondering, I got the + in y+1 because of the two negatives being together giving you a positive.